Photorespiration participates in the assimilation of acetate in Chlorella sorokiniana under high light. Issue 3 (6th October 2015) - Xie, Xiujun; Huang, Aiyou; Gu, Wenhui; Zang, Zhengrong; Pan, Guanghua; Gao, Shan; He, Linwen; Zhang, Baoyu; Niu, Jianfeng; Lin, Apeng; Wang, Guangce
Summary: The development of microalgae on an industrial scale largely depends on the economic feasibility of mass production. High light induces productive suspensions during cultivation in a tubular photobioreactor. Herein, we report that high light, which inhibited the growth of Chlorella sorokiniana under autotrophic conditions, enhanced the growth of this alga in the presence of acetate. We compared pigments, proteomics and the metabolic flux ratio in C. sorokiniana cultivated under high light (HL) and under low light (LL) in the presence of acetate. Our results showed that high light induced the synthesis of xanthophyll and suppressed the synthesis of chlorophylls. Acetate in the medium was exhausted much more rapidly in HL than in LL. The data obtained from LC‐MS/MS indicated that high light enhanced photorespiration, the Calvin cycle and the glyoxylate cycle of mixotrophic C. sorokiniana . The results of metabolic flux ratio analysis showed that the majority of the assimilated carbon derived from supplemented acetate, and photorespiratory glyoxylate could enter the glyoxylate cycle. Based on these data, we conclude that photorespiration provides glyoxylate to speed up the glyoxylate cycle, and releases acetate‐derived CO2 for the Calvin cycle. Thus, photorespiration connects the glyoxylate cycle and the Calvin cycle, and participates in the assimilation of supplemented acetate in C. sorokiniana under high light.